2022
DOI: 10.3390/ijms23073448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinically Used Microtubule Targeting Drugs on Viral Infection and Transport Function

Abstract: Microtubule targeting agents (MTAs) have been exploited mainly as anti-cancer drugs because of their impact on cellular division and angiogenesis. Additionally, microtubules (MTs) are key structures for intracellular transport, which is frequently hijacked during viral infection. We have analyzed the antiviral activity of clinically used MTAs in the infection of DNA and RNA viruses, including SARS-CoV-2, to find that MT destabilizer agents show a higher impact than stabilizers in the viral infections tested, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Noticeably, we have found that PM534 is also effective in tumor cells that upregulate tubulin βIII isotype, as it is not affected by the Cys239 to Ser239 change in the colchicine binding site. This is a known resistance mechanism emerging as a feature of aggressive and treatment-refractory cancers. ,, Notice that some of the compounds that bind deeper in the CBD are more selective for certain tubulin isotypes or bind preferentially to tubulins of other species . This ability to choose isotypes comes from some residues within the domain, like βC241 (in central hinge helix H7) and βI318 (pharmacophore center I), which are often involved in protein–drug interactions and are changed in the βIII-tubulin isotype to βS241 and βV318, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, we have found that PM534 is also effective in tumor cells that upregulate tubulin βIII isotype, as it is not affected by the Cys239 to Ser239 change in the colchicine binding site. This is a known resistance mechanism emerging as a feature of aggressive and treatment-refractory cancers. ,, Notice that some of the compounds that bind deeper in the CBD are more selective for certain tubulin isotypes or bind preferentially to tubulins of other species . This ability to choose isotypes comes from some residues within the domain, like βC241 (in central hinge helix H7) and βI318 (pharmacophore center I), which are often involved in protein–drug interactions and are changed in the βIII-tubulin isotype to βS241 and βV318, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 45 , 50 Notice that some of the compounds that bind deeper in the CBD are more selective for certain tubulin isotypes 51 or bind preferentially to tubulins of other species. 52 This ability to choose isotypes comes from some residues within the domain, like βC241 (in central hinge helix H7) and βI318 (pharmacophore center I), which are often involved in protein–drug interactions and are changed in the βIII-tubulin isotype to βS241 and βV318, respectively. PM534 does not interact with βC241, although it can establish hydrophobic contacts with βI318, which could work against overexpression of the tubulin isotype βIII.…”
Section: Discussionmentioning
confidence: 99%
“…Our theoretical and numerical predictions thus present numerous possibilities for superradiance- and subradiance-enabled metabolic regulation, communication, and control in and between cells (see Table S3) and with external agents that interact with the cytoskeleton at various stages of cellular growth and replication . We complement the theory and computation with experimental measurements of fluorescence QY in tubulin and MTs, which point to a significant increase from the former to the latter, in line with the numerical predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Peptidic probes combined a cell penetrating region and a kinesin binding domain and were labelled at the N -termini with Cy5 to provide a fluorescent kinesin binding peptide. Their synthesis and labelling has been previously described ( Oliva et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%